Gambaran Rasa Percaya Diri Warga Belajar pada Program Pendidikan Keaksaraan Fungsional di PKBM Diknaker - Rika Fadila; Irmawita Irmawita (Universitas Negeri Padang, 2018)
The research was distributed by the phenomenon of functional literacy program success rate base on the South coast of Diknaker PKBM. This is evidenced by the high learning outcomes acquired citizens learn. Researchers suspect that the cause of the success of these KF due to high confidence that is owned by the citizens of learning. Type of this research is quantitative descriptive research. Withdrawal technique used is the sample census, all of the population sample was made as many as 20 people, which is called the respondent. Using data collection techniques interviews that is in the form of structured interviews. While the data analysis techniques using the formula percentages. From the results of the study found that the confidence of citizens learning related to believe in its own ability, courageous decisions, courageous and suggested categorized either. Keywords: Self-Confidence, Learning Outcomes